(untitled) (Psychology Travelogs, 2022)
Today, higher education is not only a formal type of education, but also a special level of personality formation, realization of abilities, development of individual culture of a professional by involving the future specialist in the innovative achievements of science. Professional mobility as readiness for self-education, self-development, self-realization enables the professional development of the future psychologist, ensuring his competitiveness in the labor market. Having analyzed the philosophical, psychological and pedagogical literature related to the problem of the development of the professional mobility of the future psychologist in the institution of higher education, we substantiated the psychological conditions for the development of this integrative characteristic: sustainable motivation for constant professional self-development and self-realization; activation of independent educational and cognitive work of future psychologists based on reflective assessment of their own activity; development of creative potential of students of higher education.